Analisis Model Diversi Melalui Restorative Justice Pada Anak Pelaku Tindak Pidana Terorisme Dalam Perspektif Maqashid Syari’ah - Mohammad Farid Fad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
The act of terrorism involving children certainly raises its own concerns. How not, if the child is faced with a formal justice process then besides he will lose his independence, he will also lose his future because of stigmatization as a terrorist who is attached for life. However, if the model of diversion through restorative justice is adopted, the legal process will be blocked by the provisions of Article 7 paragraph (2) of Law No. 11 of 2012 concerning the Child Criminal Justice System. Then what is the meeting point between the two? How is this diversion approach in the perspective of Maqashid al-Shari'ah? This article tries to describe the diversion model through a restorative justice approach in the perspective of maqashid al-shari'ah. The type of method used in this study is a qualitative method. The data collection technique used is library research sourced from various literatures such as books, books and journal articles. After the data is collected, an analysis will be carried out using descriptive-analytical methods. This study concludes that restorative justice through a diversion model is in line with the principles of maqashid al-syari'ah, this legal approach aims to help children of terrorists realize, feel and restore humanitarian relations that were damaged between the perpetrators and victims. This is due to the fact that the child of the terrorist is not an actor in the real sense, but he is the real victim of the results of his parents' indoctrination or other parties.